Potential value of earth satellite measurements to oceanographic research in the Southern Ocean - IOC. International Coordination Group for the Southern Ocean, 2nd session, Buenos Aires, 1974; McClain, E. Paul (1974)
Incl. bibl. Meeting paper on the use of artificial satellites in oceanographic research - Considers measuring methods by remote sensing for collecting data on surface water temperatures and ice in the polar regions of the Antarctic Ocean, examines scientific instruments used and provides characteristics of various satellite sensors